2020
DOI: 10.1111/ans.15955
|View full text |Cite
|
Sign up to set email alerts
|

Is radical resection of hilar cholangiocarcinoma plus partial resection of pancreatic head justified for advanced hilar cholangiocarcinoma?

Abstract: Background To outline our experience with the radical resection of hilar cholangiocarcinoma (HCCA) combined with the partial resection of the pancreatic head (RRHCCAPRPH) as a treatment for HCCA with distal bile duct involvement and to appraise the feasibility of this challenging procedure. Methods Between 2007 and 2017, 205 patients with HCCA who underwent curative surgery at our hospital were included. Among the patients, extrahepatic bile duct resection combined with hepatectomy (EBDRH), RRHCCAPRPH and hepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…The effects of the biliary stasis on the liver remnant include impaired function of hepatocyte mitochondria, impaired activity of microsomial mixed function oxidase, and in general increased predisposition to endotoxemia[ 5 , 29 ]. The role of preoperative biliary drainage of jaundiced patients scheduled for PD remains questioned[ 11 ]. However, authors suggested that biliary drainage may be appropriate before HPD, especially when major hepatectomy is planned[ 10 , 11 , 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The effects of the biliary stasis on the liver remnant include impaired function of hepatocyte mitochondria, impaired activity of microsomial mixed function oxidase, and in general increased predisposition to endotoxemia[ 5 , 29 ]. The role of preoperative biliary drainage of jaundiced patients scheduled for PD remains questioned[ 11 ]. However, authors suggested that biliary drainage may be appropriate before HPD, especially when major hepatectomy is planned[ 10 , 11 , 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…The role of preoperative biliary drainage of jaundiced patients scheduled for PD remains questioned[ 11 ]. However, authors suggested that biliary drainage may be appropriate before HPD, especially when major hepatectomy is planned[ 10 , 11 , 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations